BIOMONITORING PENCEMARAN UDARA MENGGUNAKAN BIOINDIKATOR LICHENES DI KOTA MADIUN - Ihrom, Anikhotul; Sulistyarsi, Ani (Jurnal Florea, 2015)
Bioindicators can be used to determine levels of air pollution of an area by analyzing the content ofpollutants lead in bioindicators. Lichenes growing on the bark as bioindicators for measuring theconcentration of lead in air pollutants resulting from motor vehicle emissions. The aim of research to determine differences in the levels of lead (Pb) using bioindicators Lichenes Madiun. Samples weretaken by random sampling technique. Pb content measurement using Atomic AbsorptionSpectrophotometer (AAS). The results showed Pb levels in different areas of the City of Madiun thereare significant differences. Traffic levels affect the levels of Pb .Keywords: Lichenes, lead, bioindikator